Liposomal bupivacaine vs. Ropivacaine for wound infiltration on chronic postsurgical pain after video-assisted thoracoscopic lung surgery: protocol for a randomized, double-blind, controlled trial - Han-xue Zhao; Wei Dou; Xin-tong Meng; Yi-fan Shi; Xi-sheng Shan; Fu-hai Ji; Shao-mu Chen; Ke Peng (Annals of Medicine)
Introduction Chronic postsurgical pain (CPSP) remains a significant challenge for patients undergoing video-assisted thoracoscopic surgery (VATS), compromising their quality of life and postoperative recovery. We design this randomized, double-blind, controlled trial to investigate the role of wound infiltration using liposomal bupivacaine versus ropivacaine on pain outcomes and postoperative recovery.Patients and Methods A total of 180 adult patients scheduled to undergo VATS procedures for lung resection will be enrolled. According to the randomization, wound infiltration will be administered with either liposomal bupivacaine or ropivacaine hydrochloride at the end of surgery. Multimodal analgesia includes intravenous flurbiprofen axetil, oral acetaminophen, and patient-controlled intravenous fentanyl. Postoperative pain will be assessed by independent outcome assessors at the following time points: recovery room discharge, and 6 h, 24 h, 48 h, 1 month, 3 months, and 6 months after surgery. The primary outcome is the incidence of CPSP at 3 months. Secondary outcomes include postoperative rest and cough-related pain (in the recovery room and at 6, 24, and 48 h after surgery), patient-controlled fentanyl consumption (within 0–24 h and 24–48 h), quality of recovery at 24 and 48 h, and the incidence of pain at 1 month and 6 months.Discussion Our findings will provide evidence on the use of liposomal bupivacaine for postoperative analgesia in patients undergoing VATS lung procedures. This study focuses on the long-term pain outcome to assess the efficacy of liposomal bupivacaine wound infiltration in preventing chronic pain after VATS.Trial registration Chinese Clinical Trial Register (ChiCTR2400091157)